Pemberdayaan Masyarakat dalam Mengenal Pewarna dan Pemanis Sintetik Berbahaya - Yuszda K Salimi; Opir Rumape; Najmah Najmah (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
Additives as food additives that are intentionally added in small quantities for food quality and are available in natural and synthetic ingredients. Synthetic dyes and sweeteners are widely circulating in the community, synthetic food ingredients are in great demand in terms of taste and attractive color appearance without regard to nutritional and health values. Community empowerment aims to increase understanding and knowledge about harmful synthetic dyes and sweeteners in food in the surrounding environment. Community service activities were carried out in Molotabu Village, Kabila sub-district, Bone Bolango Regency, Gorontalo Province. The method used is socialization including the delivery of material by resource persons and followed by discussion. The participants were PKK mothers in Molotabu village, the outreach activities went well from the beginning to the end of the activity the participants were very enthusiastic, the participants got to know additives and various synthetic dyes and sweeteners that are harmful to health and their negative impacts, the knowledge and insight of the community increased regarding the additives used hazardous to health so that participants are vigilant and selective in choosing and buying food and drinks that indicate synthetic dyes and sweeteners in their surroundings.